SISTEM GOWE PADA SUKU BANGSA MANDOBO DI KAMPUNG MAWAN KABUPATEN BOVEN DIGOEL - Wonopka, Woni Eva Vera (Universitas Sam Ratulangi, 2015)
Culture as a concept which coalesce in human life that always associated with life need. Culture that is a set of the system of knowledge the idea or system serves become guidelines for the attitude of his life and human behavior as members or residents of his social unity, growing, develops, and changed in accordance with the needs of human life. Before humans began to recognize social life, all life need sought own without the aid of others. But after getting forward life, human realized that they could not meet the needs of his own life. In the Mandobo tribe hunting or also in Mandobo language in call with â€œgoweâ€ is livelihoods their lives everyday, which of the results of hunting they can meet the needs of their lives everyday. Usually hunt conducted by the male meanwhile women vegetables gather, the tubers of which are in their neighborhood. Hunting means Mandobo tribe still use traditional means with simple tools. Their Mawan was a village in Kabupaten Boven Digoel still maintaining the gowe. Gowe system on the Mandobo tribe in Mawan village it is the activities carried out by hereditary than their ancestors. Basically gowe system is a form of traditional economic system that can be viewed from the perspective of procurement, the distribution, and the use of objects a need or in other words the economy system in approach through production pattern, the distribution pattern and the pattern consumption. Keywords: culture, hunting, gowe